The politics of integrating gender to state development processes: Trends, opportunities and constraints in Bangladesh, Chile, Jamaica, Mali, Morocco and Uganda - Anne Marie Goetz (United Nations Research Institute for Social Development (UNRISD), 1995)
This paper provides an assessment of efforts in six of the seven countries to improve public accountability to women in the development process. The paper begins with a brief theoretical discussion of feminist perspectives on the developmentalist state (Part I). It then goes on to provide an overview of some of the more prominent political, economic and social trends of the past two decades, against which efforts have been made to institutionalize gender in state development processes (Part II). In the main body of the paper (Part III), the author provides a historical and comparative analysis of efforts in the six case study countries to institutionalize gender concerns. The picture that emerges is one of extraordinarily fractured trajectories of institutionalization within the public administration. Most of the gender units within government bureaucracy that are studied here have a mandate to pursue their agenda across other government departments - a project that is sometimes called "mainstreaming". For this they have devised a range of policy instruments (e.g. gender guidelines, gender training) intended to bring about gender-sensitive institutional, policy and operational changes across the public sector in order to make responsiveness to women's interests a routine part of each sector's activities. Despite significant efforts, the attempts to routinize gender concerns have for the most part been ineffective because gender units have been unable to provide the necessary incentives to encourage a positive reception in other departments. Some of the critical areas for gender mainstreaming considered in the paper include the national development plan and budget which constitute important public statements expressing politically selected priorities for change and progress, and are based on a macro-economic framework designed to create the conditions under which this national vision can be realized. Efforts so far in the countries studied have failed to ensure a systematic connection between national policy commitments to the integration of gender in development and the budgetary allocations that are necessary to realize those commitments. The chronic short-staffing of gender administrative units, compounded by their weak analytical skills, has tended to contribute to this failure. Equally important, however, has been the political weakness of gender constituents outside the state. In the politics of policy-making a critical point of leverage on decision makers is popular pressure and public opinion - the presence of an active constituency.
Keywords: 330